Wisala Meru Musical Artwork | Karya Musik Wisala Meru - Agung SemaraBawa; I Ketut Sudhana (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Wisala Meru Musical Artwork is a new creative composition that is packaged with a traditional nuance. The title Wisala Meru has the meaning of a sacred building or Meru, famous for its majesty, height, and splendor. This work is an interpretation of the Meru shrine, which has overlapping layers, getting smaller and smaller upwards until it rises to resemble the shape of a mountain. This work was inspired by the concept of Tri Angga (head, body, and feet) in Meru which later became the concept in Wisala Meru's musical composition. Wisala Meru's work uses the gamelan Semar Pegulingan as a medium of expression and adds kempur instruments with gupekan and cedetan drums. The cultivation of musical elements in this musical work be focused on cultivating rhythm, melody, tempo, sound color, dynamics, and the soul of each material. The process of creating this work is carried out in five stages inspired by I Wayan Dibia's method in the Art Creation Methodology book, namely: Inspiration (Ngawirasa), Exploration ( Ngewacak), Conception (Planning), Execution (Ngawangun), and the last is Ngebah (Maedeng). This work is manifested in the form of creative percussion which is still grounded in the realm of tradition, the renewal contained in this work lies in the musical formulation that uses the patets of the gamelan Semar Pegulingan to realize a replica of the sacred building of Meru. So that Wisala Meru's musical artwork is an interpretation of the shape of the Meru building with Semar Pegulingan as a medium of expression into magnificent musical art.